2013
DOI: 10.1021/jo401847v
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies on a Carbenoid Mechanism for the Doering–Moore–Skattebøl Reaction

Abstract: The reaction of geminal dihalocyclopropanes with metals or alkyllithiums affords carbenoids which undergo low-temperature ring opening to allenes; this is known as the Doering-Moore-Skattebøl reaction. DFT and CCSD(T)//DFT computations have been used to model the structure, coordination state, and ring opening of 1-bromo-1-lithiocyclopropane as a model for cyclopropylcarbenoid chemistry. Both implicit (PCM) and explicit solvation models have been applied. Carbenoid ring opening is similar to the process predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In general, the lithium–bromine exchange reaction of 1,1‐dibromospirapentanes ( 1 ) with MeLi affords the corresponding allenes ( 2 ) as major products via the formation of spiropentanoids 5a , 5b , 5c , 5d , 5e , 5f , 5g , 5h , 5i , 5j (Route 1). This method, so‐called DMS reaction, is well documented in the literature . Interestingly, lowering the reaction temperature to −55°C leads to the formation of either cyclobutenes 3 (Route 2) or the compounds of 4 (Route 3) depending on the substituents of the spiropentane rings (Scheme ).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…In general, the lithium–bromine exchange reaction of 1,1‐dibromospirapentanes ( 1 ) with MeLi affords the corresponding allenes ( 2 ) as major products via the formation of spiropentanoids 5a , 5b , 5c , 5d , 5e , 5f , 5g , 5h , 5i , 5j (Route 1). This method, so‐called DMS reaction, is well documented in the literature . Interestingly, lowering the reaction temperature to −55°C leads to the formation of either cyclobutenes 3 (Route 2) or the compounds of 4 (Route 3) depending on the substituents of the spiropentane rings (Scheme ).…”
Section: Introductionmentioning
confidence: 95%
“…Theoretical computations predict modestly exergonic dimerization of the cyclopropylidenoids, with or without solvation, and the dimer appears to be the most likely reactive species in solution. Calculated energy barriers to ring opening are only modestly affected by solvation or by dimer formation …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several years ago, we reported that the Doering–Moore–Skattebøl (D–M–S) reaction 1 3 of 1,1-dibromo-1a,9b-cyclopropa[ l ]phenanthrene ( 1 ) with butyllithium and copper(II) chloride in THF gave the hydrocarbon 2 , a cyclotetramer of the strained allene dibenzocycloheptatetraene ( 5 ), as shown in Scheme 1 . 4 Also formed as a byproduct in this reaction is the ether 6 which could be rationalized as an insertion reaction of dibenzonarcarnylidene ( 4 ), or a carbenoid equivalent 3 that qualitatively behaves like the carbene, 5 , 6 with the THF used as solvent. We have also previously reported the ylide-forming reaction of 4 with THF.…”
mentioning
confidence: 99%